Strategy for Packaging Political Content on The Saeful Zaman Youtube Channel - Herlina, Rita; Simabur, Lisda Ariani; Ningsih, Fuji Fera Rahayu; Darmawan, Andri (INTERACTION: Jurnal Pendidikan Bahasa, 2023)
Many political events that Saeful Zaman Channel can discuss and criticize daily are the background of this research with the theme "Strategy for Packaging Political Content on the Saeful Zaman YouTube Channel". This research aims to determine the content packaging strategy in terms of the settings on the YouTube account, the stages of content production, and the benefits of political content for viewers. This research method is a qualitative method with a case study approach. Data collection techniques are interviews, observation and document analysis. The results of the study show that a content packaging strategy can be created through efforts to package account settings on YouTube Studio as a media identity that must be able to radiate a positive image to the public supported by story ideas that can speak for the public interest, then during live streaming it is important for YouTubers to show interaction with the audience, through the YouTuber's response to each viewer's comment as well as analyzing the comments, then from the benefits of content it must be able to provide more value than just conveying information, namely being a means to change people's mindset so that they are more sensitive and concerned about the current social and political situation.